2014
DOI: 10.3329/bjp.v9i4.20610
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer potential of banana flower extract: An <i>in vitro</i> study

Abstract: Banana (Musa paradisiaca) flower is rich in phytochemicals (vitamins, flavornoids, proteins) and has anti-oxidant properties. The anti-cancer activity of banana flower extract has been evaluated on the cervical cancer cell line HeLa. The anti-proliferative effects were evaluated by MTT assay. The extract was further purified by TLC and characterized by LC-MS method. The ethanol extract had significant cytotoxicity to HeLa cells with an IC50 of 20 µg/mL. By thin layer chromatography we could isolate three fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…It possesses several medicinal properties which include antilithiatic, antibacterial, antidiabetic, antiulcer, anti-diarrheal, hypocholesterolaemic, hepatoprotective, anti-snake venom, wound healing, hair growth promoting, antifungal and anti-menorrhagia activity [16]. due to the presence of anti-cancer activity Musa × paradisiaca L can be prove effective against cervical carcinoma and malignant melanoma [17].…”
Section: Introductionmentioning
confidence: 99%
“…It possesses several medicinal properties which include antilithiatic, antibacterial, antidiabetic, antiulcer, anti-diarrheal, hypocholesterolaemic, hepatoprotective, anti-snake venom, wound healing, hair growth promoting, antifungal and anti-menorrhagia activity [16]. due to the presence of anti-cancer activity Musa × paradisiaca L can be prove effective against cervical carcinoma and malignant melanoma [17].…”
Section: Introductionmentioning
confidence: 99%
“…Like iridomyrmecin, oleanolic acid methyl ester derivative shows anti-cancer effect in HeLa cervical cancer cells which is mediated through apoptosis induction and reactive oxygen species production (Song et al, 2015). The ethanol extract of banana (Musa paradisiaca) flower or Cordia dichotoma leaf also shows anti-cancer activity on the cervical cancer cell line HeLa (Nadumane and Timsina, 2014;Rahman and Hussain, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…2009 ), various other studies have reported a myriad of biological activity that also includes a potent anticancer activity (Baliga 2011 ; Pekamwar et al. 2013 ; Nadumane & Timsina 2014 ). In order to study the role of these extracts on tumour growth and inhibition of VEGF-induced angiogenesis in vitro , two invasive ductal breast carcinoma cell lines, namely, MCF-7, MDA-MB-231 (triple-negative) and human umbilical vein endothelial cells (HUVEC) were used.…”
Section: Introductionmentioning
confidence: 97%